SIFa and its receptors play a possibly stimulatory role during ovarian development of the mud crab Scylla paramamosain - Chen, Sijia; Tang, Yiwei; Lu, Li; Gong, Shaoming; Liu, An; Ye, Haihui (Frontiers in Marine Science, 2024)
SIFamide is an amidated neuropeptide with a conserved Ser-Ile-Phe structure at its C-terminal, which is crucial in insect courtship, sleep and feeding in insects. However, little information exists regarding its function in crustaceans. This study aimed to identify the cDNA of Sp-SIFa and its two putative receptors (Sp-SIFaR1 and Sp-SIFaR2) in the mud crab Scylla paramamosain. The expression profiles of Sp-SIFa and its receptors signaling were investigated to explore their potential roles. The results indicated that Sp-SIFa was expressed primarily in the nervous tissues and the midgut, and Sp-SIFaR1 was extensively expressed in the eyestalk ganglion, cerebral ganglion, hepatopancreas and the ovary whereas Sp-SIFaR2 was restricted to the eyestalk ganglion and ovary. The Sp-SIFa expression in the cerebral ganglion was significantly increased at the late vitellogenic stage during the ovarian development. The expression patterns of Sp-SIFaR1 and Sp-SIFaR2 in the ovary were similar to Sp-SIFa, indicating a potential function in regulating ovarian development. Subsequently, in vitro and in vivo experiments were performed to further support this hypothesis. The expression of Sp-Vg and Sp-VgR was significantly induced by Sp-SIFa peptide in vitro and in vivo. Moreover, prolonged injection of the Sp-SIFa peptide caused a significant increase in Sp-VgR expression, oocyte diameter and gonadal development index, demonstrating a possible stimulatory effect on ovarian development. In conclusion, our results suggest that Sp-SIFa may regulate ovarian development by promoting Vg biosynthesis and oocyte uptake in the mud crab S. paramamosain.